Best practices of high performing higher education institutions in the Philippines towards the development of harmonized quality-assured instructional leadership framework - Aquino, John Michael Del Rosario (Frontiers in Education, 2025)
Instructional leadership is vital for ensuring quality teaching and learning in Higher Education Institutions (HEIs), particularly in Teacher Education Institutions (TEIs) that aim to sustain accreditation standards and enhance students' performance. This study was conducted from July 2023 to April 2024 in the Luzon Region, Philippines, aimed to develop a harmonized instructional leadership framework based on the best practices of six high-performing HEIs—two State Universities and Colleges (SUCs), two Private Institutions, and two Local Universities and Colleges (LUCs). Institutions were purposively selected based on stringent criteria, including accreditation status (PAASCU, AACCUP, ALCUCOA), ISO certification, Centers of Development/Excellence, national and global rankings, and consistent Licensure Examination for Teachers (LET) performance. Using a qualitative comparative multi-case study approach, data were gathered from 88 participants (administrators, faculty, and students) through validated semi-structured interviews, adding document analysis, and thematic analysis with intercoder validation. A panel of twelve (12) experts in leadership, management, curriculum, and instruction reviewed the framework. Findings led to a harmonized quality-assured instructional leadership framework with six phases (6) and twenty (20) interrelated components, promoting efficiency, adaptability, and continuous improvement. This structured, systematic and evidence-based guide supports instructional leaders in aligning institutional mechanisms with excellence standards, adaptable across diverse HEI contexts nationwide.